1981
DOI: 10.1097/00004032-198110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of Population Exposures Due to Radon in Public Water Supplies in the Area of Houston, Texas

Abstract: An estimate of the incremental population lung exposures (WLM) attributable to the domestic use of ground waters containing z2zRn is made for the vicinity of Houston, Texas. Because of the complexity of the water distribution system, extensive water sampling was required to characterize the concentration of radon in the water in various areas. Models describing the transfer of radon from water to indoor air and the resulting indoor concentrations were developed and experimentally tested. Census data on populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…1 " 5 In addition, there have been studies of indoor radon exposure as a result of water-born radon-222, another highly volatile substance. 6 "* These studies indicate that exposure to volatile chemicals in tap water by inhalation may be as large as or larger than exposure from fluid ingestion. The contaminants available in the indoor air are released by showers, baths, toilets, dishwashers, washing machines, and cooking.…”
Section: Introductionmentioning
confidence: 96%
“…1 " 5 In addition, there have been studies of indoor radon exposure as a result of water-born radon-222, another highly volatile substance. 6 "* These studies indicate that exposure to volatile chemicals in tap water by inhalation may be as large as or larger than exposure from fluid ingestion. The contaminants available in the indoor air are released by showers, baths, toilets, dishwashers, washing machines, and cooking.…”
Section: Introductionmentioning
confidence: 96%
“…He points out the need for refining present estimates of indoor air exposure to VOCs derived from potable water sources by, inter alia, more accurately accounting for the chemical characteristics that affect the rate and extent of volatilization. In order to account for the different properties of VOCs, McKone (3,5,6) proposed a relationship which adjusts the measured transfer 2 ,it efficiency (the fraction volatilized) for radon (7,8) to that for any VOC using the Henry's law constant and liquid and gas diffusivities. Although the relationship was only 'intended to be approximate it does not adequately account for gas-phase resistance (9).…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious route of exposure to contaminants is by ingestion; however, dermal and inhalation exposure may also occur within the home. Several studies have shown that showering increases the likelihood that an organic compound will be volatilized, resulting in human exposure beyond that occurring from ingestion (Backer et al, 2000; Giardino & Hagman, 1996;Kerger et al, 2000;Moya et al, 1999;Prichard & Gesell, 1981). For example, in one study, the blood levels of trihalomethane were highest among individuals showering for 10 min, intermediate for individuals bathing for 10 min, and lowest among those who drank 1 L water from the same source over a 10-min period (Backer et al, 2000).…”
mentioning
confidence: 99%